Costruire “teste ben fatte” con la didattica a distanza: riflessioni pedagogiche sugli usi della DaD, dentro e fuori dall’emergenza - Di Bari, Cosimo (Studi sulla Formazione/Open Journal of Education, 2021)
The article deals with the topic of distance learning and reflects on the strategies to promote critical thinking. The emergency of Covid 19 pandemic suddenly forced the school to deal with the use of technologies, even if many teachers weren’t ready to set their lesson on-line. The text reflects on the contemporary didactic and tries to identiffy the features that teaching should have to promote the building of “bien faits” heads.